Digitalization and Platforms in Agriculture: Organizations, Power Asymmetry, and Collective Action Solutions - Martin Kenney; Hiam Serhan; Gilles Trystram (The Research Institute of the Finnish Economy (ETLA), 2020)
Technologies such as digitally-equipped agricultural equipment, drones, image recognition, sensors, robots and artificial intelli-gence are being rapidly adopted throughout the agrifood system. As a result, actors in the system are generating and using ever more data. While this is already contributing to greater productiv-ity, efficiency, and resilience, for the most part, this data has been siloed at its production sites whether on the farm or at the other nodes in the system. Sharing this data can be used to create value at other nodes in the system by increasing transparency, traceabil-ity, and productivity. Ever greater connectivity allows the sharing of this data with actors, at the same node in the value chain, e.g., farmer-to-farmer, or between different nodes in the value chain, e.g., farmer-to-equipment producer.The benefits of data sharing for efficiency, productivity and sus-tainability are predicated upon the adoption of an online digital platform. The conundrum is that, as the intermediary, the owner of a successful platform acquires significant power in relationship to the platform sides. This paper identifies five types of platform business models/ownership arrangements and their benefits and drawbacks for the various actors in the agri-food system and, in particular farmers. The types discussed are: 1) venture capital fi-nanced startups; 2) existing agro-food industry firms including equipment makers such as John Deere, agrochemical/seed con-glomerates such as Bayer/Monsanto, and agricultural commod-ity traders such as ADM and Cargill; 3) agricultural cooperative such as InVivo in France; 4) various specially formed consortia of diverse sets of agri-food system actors including farmers, and 5) the internet giants such as Amazon, Microsoft and Google. The pa-per assesses the business models for each of these organizational forms. Finally, we describe the drawbacks each of these organiza-tional forms have experienced as they attempt to secure adoption of their particular platform solution.
Keywords: Q1; Q13; L6; L66; 330; Digitization; Platform Economy; Agriculture; Agri-food systems; Cooperatives; Platform